Prevalence and characteristics of depression in mild cognitive impairment: the Sydney Memory and Ageing Study. (4th September 2012) - Shahnawaz, Z.; Reppermund, S.; Brodaty, H.; Crawford, J. D.; Draper, B.; Trollor, J. N.; Sachdev, P. S.
<x xml:space="preserve">Abstract</x> Shahnawaz Z, Reppermund S, Brodaty H, Crawford JD, Draper B, Trollor JN, Sachdev PS. Prevalence and characteristics of depression in mild cognitive impairment: the Sydney memory and ageing study. Objective: Depression might be a risk factor for dementia. However, little is known about the prevalence of depressive symptoms in mild cognitive impairment (MCI) and whether mood or motivation‐related symptoms are predominant. Method: A total of 767 non‐demented community‐dwelling adults aged 70–90 years completed a comprehensive assessment, including neuropsychological testing, and a past psychiatric/medical history interview. Depressive symptoms were assessed using the Geriatric Depression Scale (GDS) and Kessler Psychological Distress Scale (K10). Exploratory factor analysis was performed on the GDS and K10 to derive 'mood' and 'motivation' subscales. Results: A total of 290 participants were classified as having MCI and 468 as cognitively normal (CN). Participants with MCI reported more depressive symptoms, and more MCI participants met the cut‐off for clinically significant symptoms, relative to CN participants. Those with amnestic MCI (aMCI), but not non‐amnestic MCI, had more depressive symptoms and were more likely to meet the cut‐off for clinically significant depressive symptoms, relative to CN participants. Participants with MCI reported more mood‐related symptoms than CN participants, while there were no differences between groups on motivation‐related symptoms. Conclusion: Individuals with MCI, especially aMCI, endorse more depressive symptoms when compared with cognitively intact individuals. These findings highlight the importance of assessing and treating depressive symptoms in MCI.